PENERAPAN METODE ELECTRE II DALAM MENCARI FAKTOR HAMBATAN SISWA SULIT BERKONSENTRASI DALAM MATA PELAJARAN - Putri, Nirwanda Desnila; Poningsih, Poningsih; Irawan, Irawan (STMIK Budi Darma, 2019)
Education is an effort specifically by goverments to provide the generation with appropriate academic potentials through which the successors attain the required capabilities to survive the natiions. .The process this transfer of information is carried out in school. But still, every thing does not run as smoothly as expected. The purpose of this research is to identify the problems serving as barrcades affecting the students to achieve the goals of learning.For a solution, the writer suggests the use of algorithm ELECTRE II as calculation to discover the best alternative. This method is implemented into an application of Vb Net 2010. The result obtined is A03 having best alternative while the biggest average is friend.Keywords: Decision Support System, Electre ii, Vb Net, Concentration, Students.